АНАЛІЗ НИЗЬКОЧАСТОТНИХ КОЛИВАНЬ В ЕНЕРГОСИСТЕМІ З ВИКОРИСТАННЯМ ВЕЙВЛЕТ-ПЕРЕТВОРЕННЯ - Марченко, А.А.; Тимохін, О.В.; Тимохіна , А.О. (Інститут електродинаміки НАН України, Київ, 2015)
Work is devoted to the mathematical analysis of low-frequency oscillations that can occur in power systems with significant perturbations. The classical approach based on the use of the mathematical approach of the Fourier transform, and more modern which is based on wavelet transforms. Article presents analysis of real data from devices wide area measurement systems, using referred above two mathematical apparatus. Consequently, results gave possibility to make conclusion of comparative analysis of this two approaches, in particular, their advantages and disadvantages. References 7, figures 5.